2007
DOI: 10.1021/bi062066y
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Crystal and Molecular Dynamics Simulation Structures of Human Carbonic Anhydrase II:  Insights into the Proton Transfer Mechanism,

Abstract: Human carbonic anhydrase II (HCA II) is a zinc-metalloenzyme that catalyzes the reversible interconversion of CO 2 and HCO 3 -. The rate-limiting step of this catalysis is the transfer of a proton between the Zn-bound solvent molecule and residue His64. In order to fully characterize the active site structural features implicated in the proton transfer mechanism, the refined X-ray crystal structure of uncomplexed wild type HCA II to 1.05 Å resolution with an R cryst value of 12.0% and an R free value of 15.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
231
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(245 citation statements)
references
References 30 publications
14
231
0
Order By: Relevance
“…In addition to the electrostatic and related pK a changes that occurred also produced a shorter, unbranched chain of hydrogen-bonded waters that connect ZW to the proton shuttling residues His64. These electrostatic changes and unbranched water network boost the proton transfer activity of HCA II Tyr7Phe mutants (Fisher et al, 2007b). As reported in Table III, the values of k B for TS2 and TS4 are even better than for Tyr7Phe alone at 5.6 and 4.9, respectively.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In addition to the electrostatic and related pK a changes that occurred also produced a shorter, unbranched chain of hydrogen-bonded waters that connect ZW to the proton shuttling residues His64. These electrostatic changes and unbranched water network boost the proton transfer activity of HCA II Tyr7Phe mutants (Fisher et al, 2007b). As reported in Table III, the values of k B for TS2 and TS4 are even better than for Tyr7Phe alone at 5.6 and 4.9, respectively.…”
mentioning
confidence: 80%
“…Data processing and reduction were done with either d*TREK or the HKL2000 suite of programs (Otwinowski and Minor, 1997;Pflugrath, 1999). The starting model was derived from protein data bank (PDB) accession number 2ili with all the waters and Zn removed, and with the mutated residues changed to Gly (Fisher et al, 2007b). All the structures were refined using PHENIX and manual inspection and model building was done using Coot (Emsley and Cowtan, 2004;Adams et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Many previous structural studies of hCAII have shown that His-64 occupies two conformations, termed "in" and "out." Generally it has been seen that the "in" conformation is favored, although there may be pH effects on the ratio of "in" to "out" (10,13). In both the holoCO 2 -bound and the apoCO 2 -bound structures, His-64 was seen to have a preference for the "out" conformation.…”
Section: Methodsmentioning
confidence: 96%
“…10-l drops of equal amounts of protein and precipitant were equilibrated against precipitant solution (1.3 M sodium citrate, 100 mM Tris-HCl, pH 7.8) by vapor diffusion at room temperature (ϳ20°C) (13). Crystals grew to ϳ0.2 ϫ 0.2 ϫ 0.5 mm in size after ϳ5 days.…”
Section: Methodsmentioning
confidence: 99%
“…Structure Determination-All the crystal structures were determined by molecular replacement methods using wt CA II (PDB code 2ili) [29]. The initial rigid body, individual coordinate and atomic displacement parameter…”
Section: Introductionmentioning
confidence: 99%